2012
DOI: 10.2217/crc.12.45
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of colorectal cancer awareness and knowledge with colorectal cancer screening

Abstract: SUMMARY Aim The aim was to describe the association of awareness and knowledge with participation in colorectal cancer (CRC) screening. Materials & methods Telephone survey research was conducted with South Carolina (USA) residents aged 50–75 years using a 144-item instrument. Data were analyzed with SAS and Stata. Adjusted odds ratios are reported. Results Respondents (n = 1302) had heard of CRC screening (96%) and exhibited high levels of CRC awareness and knowledge; only 74% had ever been screened. Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 69 publications
1
36
4
1
Order By: Relevance
“…Coughlin et.al [29] found that screening rates were lowest for Hispanic women with an annual household income of less than $15,000. In addition, in studies with different racial/ethnic groups, such as Hispanics, African Americans, Asians, and American Indians, the likelihood that a patient undergoes screening tests is lower in patients with lower income [30]. Both race and economic status appear to play roles not only in CRC knowledge, but also in CRC screening and incidence rates [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coughlin et.al [29] found that screening rates were lowest for Hispanic women with an annual household income of less than $15,000. In addition, in studies with different racial/ethnic groups, such as Hispanics, African Americans, Asians, and American Indians, the likelihood that a patient undergoes screening tests is lower in patients with lower income [30]. Both race and economic status appear to play roles not only in CRC knowledge, but also in CRC screening and incidence rates [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, health insurance coverage appears to account for differences in CRC screening rates among racial/ethnic groups [40-41]. Furthermore, previous studies have found that adults without health insurance had the highest rate of not undergoing CRC screening compared to individuals with private or public insurance [42].…”
Section: Discussionmentioning
confidence: 99%
“…The US Preventive Services Task Force recommends men and women aged 50 years and older to participate in CRC screening by having an annual fecal occult blood test (FOBT); a flexible sigmoidoscopy, double-contrast barium enema or computed tomography colonography every 5 years; or a colonoscopy every 10 years [3]. The Healthy People 2020 goal for CRC screening adherence is 70.5% [4]. However, the estimated percentage of individuals adhering to CRC screening ranges from 47 to 66% depending on the data source, sex, race and ethnicity [5–10].…”
mentioning
confidence: 99%
“…Hébert et al ., found a CRC mortality-to-incidence ratio, an indicator of survival that incorporates both incidence and mortality, among AAs of 0.418 (95% CI: 0.390–0.447), whereas the mortality-to-incidence ratio was only 0.344 (95% CI: 0.330–0.360) among European–Americans (EAs); this difference was statistically significant [15]. Although rates of CRC screening are increasing in the USA, one possible explanation for the racial differences in CRC incidence and mortality are racial disparities in CRC screening [4]. Studies, including those from the Behavioral Risk Factor Surveillance System (BRFSS), indicate increased prevalence or odds of CRC screening among EAs compared with AAs [4,6,7,1617].…”
mentioning
confidence: 99%
“…Insufficient knowledge about cancer screening guidelines and tests is a significant barrier to participation in preventive cancer screening, especially among minority populations, which contributes to disparate cancer mortality rates [4-7]. African-American women are more likely to be diagnosed at later stages of the disease [8, 9], and thus, have significantly higher mortality rates from cancer [2, 3, 10].…”
Section: Introductionmentioning
confidence: 99%